2004
DOI: 10.1088/0268-1242/19/10/l03
|View full text |Cite
|
Sign up to set email alerts
|

High conductance Ge p-channel heterostructures realized by hybrid epitaxial growth

Abstract: Strained Ge p-channel heterostructures have been realized by hybrid-epitaxial growth. Strain-tuning Si 0.4 Ge 0.6 virtual substrates were grown by ultra-high vacuum chemical vapour deposition and active layers were deposited by solid-source molecular beam epitaxy at low temperature. Following ex situ annealing, Hall effect measurements revealed a hole mobility of 1900 cm 2 V −1 s −1 at 300 K (27 000 cm 2 V −1 s −1 at 10 K), with a density of 1.8 × 10 12 cm −2 , giving a conductance in excess of current Ge hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Two designs of modulation doped heterostructure grown by reduced pressure chemical vapour deposition (RP-CVD) were used and included a normal structure (doping above the Ge channel and inverted structure (doping beneath the Ge channel). The mobility (μ H ) for the normal structure was measured to be 1.34×10 6 cm 2 /Vs with a sheet density (p s ) of 2.9×10 11 cm -2 at 1.5 K, and μ H = 3970 cm 2 /Vs and p s ~1×10 11 cm -2 for room temperature, determined from simulation using the Maximum Entropy-Mobility Spectrum Analysis (ME-MSA) method.…”
mentioning
confidence: 99%
“…Two designs of modulation doped heterostructure grown by reduced pressure chemical vapour deposition (RP-CVD) were used and included a normal structure (doping above the Ge channel and inverted structure (doping beneath the Ge channel). The mobility (μ H ) for the normal structure was measured to be 1.34×10 6 cm 2 /Vs with a sheet density (p s ) of 2.9×10 11 cm -2 at 1.5 K, and μ H = 3970 cm 2 /Vs and p s ~1×10 11 cm -2 for room temperature, determined from simulation using the Maximum Entropy-Mobility Spectrum Analysis (ME-MSA) method.…”
mentioning
confidence: 99%
“…Both low temperature (LT) [1][2][3][4][5] and room temperature (RT) [6][7][8][9][10][11][12][13][14][15] measurements have been studied in order to obtain a better understanding of the fundamental physics behind these transport properties. It is found that to obtain an improved electrical performance for sGe, a high purity Ge QW needs to be grown on a Ge-rich buffer layer with a low defect density.…”
Section: Introductionmentioning
confidence: 99%
“…Additional tailoring is, however, possible through varying the layer thickness, composition, and dopant. Critical to the device functionality and its subsequent exploitation is the quality of the buried interfaces because these can influence the overall performance [1]. To meet the semiconductor technology roadmap [2], heterostructures have continually decreased in size with concomitant increases in their complexity.…”
mentioning
confidence: 99%